Analysis of Porter's five strengths in SD Shopos Indonesia - Elsinah Elsinah; Zahruddin Zahruddin; Maftuhah Maftuhah (Institute of Computer Science (IOCS), 2023)
The purpose of this study is to describe the strategy developed by SD Shopos Indonesia in dealing with opportunities and threats of the external environment on a micro basis based on the results of Porter's Five Forces Analysis. This type of research is qualitative with a case study method. Data collection is done by interview, observation, and study documentation. From the research results on Porter's five strengths, currently, SD Shopos Indonesia has a high threat of new entrants, a low threat of substitute products, an increased threat of bargaining power of buyers, low bargaining power of suppliers, and high competition between SPK institutions. From the results of the analysis, several strategies used to maintain the existence of the institution are to apply consistent strategy, namely: (1) Providing learning using national and foreign curricula; (2) Applying national values ??and regional culture through various programs; (3) Forming small classes (less than 20 students/class) so that supervision is good; (4) Providing educational services and teaching of international standards at affordable costs; (5) Developing national, global, and environmental insights in each lesson; and (6) Providing a holistic learning experience. The conclusion is that SD Shopos Indonesia is in a position of high external environmental threat; a small opportunity is exploited with a consistent strategy in maintaining the organization's existence.